A novel low-alkali konjac gel induced by ethanol to modulate sodium release. (June 2020) - Zhou, Yun; Wu, Liangliang; Tian, Yuan; Li, Rui; Zhu, Chongyang; Zhao, Guohua; Cheng, Yongqiang
Abstract: Alcogels have attracted many attentions recently due to their versatile functions and potential applications in developing innovative semi-solid alcohol-containing products. In this study, comparisons were made in the aspect of rheology, physicochemical properties and sodium release between the conventional alkali konjac glucomannan (KGM) gels and alkali KGM alcogels prepared by mixing ethanol with KGM aqueous solution at 0.02 wt%, 0.04 wt% or 0.08 wt% Na2 CO3 . 20% (v/w) Ethanol could promote the formation of a rigid yet brittle alcogel of KGM with lower dependence of rheological response on frequency and temperature at as low as 0.02 wt% Na2 CO3 . KGM alcogels were more opaque and constructed by small highly-connected pores, which are 30% smaller in average than those of their counterparts, examined by turbidity and microstructure measurements. Although the swelling ratio of KGM alcogel was only about one third of that of conventional alkali-induced gel, there was about fourfold rise in the amount of Na + released from alcogels. The release of Na + could be probably regulated by fine-tuning the macro-properties of alcogels through controlling the alkali concentrations. Graphical abstract: Image 1 Highlights: Ethanol promoted the gelation of KGM at a low alkali concentration of 0.02 wt%. The mechanical properties of KGM gels were remarkably changed by ethanol. A more compact network structure could be found in KGM gels with ethanol. KGM alcogels presented lower swelling ratio and higher turbidity in appearance. KGM alcogels could be potentially used for the rapid release of Na + .